Analisis Tipe Kepemimpinan dalam Film “The Last Samurai” - Vigor Wirayodha Hendriwinaya (Faculty of Psychology Universitas Gadjah Mada, 2016)
This paper displays an analysis of several literature reviews. It aims to understand the types of leadership depicted in the characters of the “Last Samurai” movie. The dilemma of cultural, political, economic and military transition for Japan in approaching the modern era is an exciting scenario depicted in the “The Last Samurai” movie. Having leaders compete against each other in achieving their intended goals, made it easy for the audience to analyze their type of leadership. The types of leadership from old to modern Japan t hat competes with Western countries is shown in this movie, particularly regarding its’ effectiveness and relevance. The visionary leadership is represented by Omura, an advisor who influenced the Emperor in realizing the comparative and competitive value of the Japanese people, allowing them to compete with various innovations and develop along with the challenges of the era. The